“We don’t really know what else we can do”: Parent experiences when adolescent distress persists after the Maudsley and family-based therapies for anorexia nervosa - Wufong, Ella; Rhodes, Paul; Conti, Janet (Journal of eating disorders, 2019)
Background Maudsley Family Therapy (MFT), and its manualised version, Family-Based Therapy (FBT), are the only well-established treatment interventions for adolescent anorexia nervosa (AN), with treatment efficacy primarily measured by improvements in eating behaviours and weight restoration. A crucial component of this therapy is an intensive home-based refeeding intervention that requires a substantial commitment from parents for up to one year. While this treatment works to restore weight in a proportion of adolescents, very little is known about its impacts on family distress, relationships and identity, including in the 40% of families where the adolescent experiences ongoing eating disorder (ED) symptomatology and/or psychological distress during and post-treatment. Specifically, few studies have investigated the impacts of MFT/FBT treatment on family functioning or on how parents negotiate their identities, or who they understand themselves to be, in the context of this treatment intervention. This is a significant omission, given the substantive role assigned to parents to take responsibility for their child’s eating restoration in the first treatment phase. This study seeks to address this gap through a qualitative exploration of parents’ experiences of MFT/FBT, in cases where treatment was discontinued and/or their child continued to experience psychological distress post-treatment. Methods 13 parents participated in in-depth semi-structured interviews that scaffolded between their experiences and ways they negotiated and sustained their identities as parents within the context of MFT/FBT for their child. Interview data was analysed through a framework of critical discursive analysis to generate themes centred on these parents’ experiences and identity negotiation. Results Key findings are that MFT/FBT: (1) provided a map for therapy that initially relieved parents’ anxieties for their child and facilitated improvements in family functioning; (2) inadequately addressed parental guilt and blame with a form of externalisation of the illness; (3) perpetuated parental guilt by raising anxiety about AN and allocating responsibility for refeeding their child in phase 1 of the treatment; and (4) when ceased, left these parents struggling with an uncertain future, and fears for the wellbeing of their children. Conclusions The structure of MFT/FBT provided initial relief with some improvements in family communication patterns, however, when the adolescent experienced protracted ED symptoms and/or ongoing psychological distress post-treatment, these parents were left with uncertainty as to how to navigate their shifting roles and their child’s ongoing struggles. This research highlights the need for treatments for adolescent AN that more comprehensively address both the adolescent and parents’ psychological distress and also (re)build their senses of identity that have been challenged by AN and its effects.